2021
DOI: 10.1177/13684302211051619
|View full text |Cite
|
Sign up to set email alerts
|

A world together: Global citizen identification as a basis for prosociality in the face of COVID-19

Abstract: How do global citizens respond to a global health emergency? The present research examined the association between global citizen identification and prosociality using two cross-national datasets—the World Values Survey (Study 1, N = 93,338 from 60 countries and regions) and data collected in 11 countries at the start of the COVID-19 pandemic (Study 2, N = 5,427). Results showed that individuals who identified more strongly as global citizens reported greater prosociality both generally (Study 1) and more spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
(81 reference statements)
3
7
0
Order By: Relevance
“…The study also replicated previous findings (e.g., Barragan et al, 2021Barragan & Meltzoff, 2023Wang et al, 2023) about the predictive power…”
Section: Asupporting
confidence: 89%
“…The study also replicated previous findings (e.g., Barragan et al, 2021Barragan & Meltzoff, 2023Wang et al, 2023) about the predictive power…”
Section: Asupporting
confidence: 89%
“…Psychology plays a considerable role in human health ( Taylor et al, 1997 ; Fredrickson, 2001 ), and the present research shows peoples’ identification with all humanity is key to predicting their willingness to contribute to the health of others . That is, while much of social and personality psychology examines the nature and course of prosocial interactions within families, cultures, and societies ( Keltner et al, 2014 ), the work on identification with all humanity is consistently suggesting that there is a portion of the population, across multiple cultures, that strives for showing concern not only for their kin, community, or country, but for all humans ( McFarland and Hornsby, 2015 ; McFarland et al, 2019 ; Sparkman and Hamer, 2020 ; Barragan et al, 2021 ; Deng, 2021 ; Hamer et al, 2021 ; Wang et al, 2021 ; Feng et al, 2022 ; Zagefka, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research (Barragan et al, 2021; Marchlewska et al, 2022; Wang et al, 2021) has not yet examined how distinct factors of maximally inclusive identities (e.g., identification with all humanity, global identification) predict health-related behaviors during COVID-19. Thus, Goal 2 of the present research was to take a more granular look at associations with the “bond” and “concern” factors of identification with all humanity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, identification with a maximally inclusive ingroup (e.g., identification with all humanity, global identification) predicted greater concern over the AIDS crisis (McFarland, 2017) and the spread of dangerous diseases such as SARS and the Avian flu (Buchan et al, 2011). Recent research has also shown identification at the most inclusive level uniquely predicts personal, health-related behaviors that reduce the spread of COVID-19 (Barragan et al, 2021; Marchlewska et al, 2022; Wang et al, 2021) or helping behaviors toward others during the COVID-19 pandemic (Deng, 2021; Zagefka, 2021).…”
mentioning
confidence: 99%